Facile Synthesis of Thienoacenes via Transition-Metal-Free Ladderization - Feofanov, Mikhail; Akhmetov, Vladimir; Takayama, Ryo; Amsharov, Konstantin (Journal of Organic Chemistry, 2021)
Herein, we report a facile transition-metal-free approach to sulfur-containing heteroacenes from fluorinated oligophenylenes. Unlike most existing methods, the presented approach is not restricted to simple dibenzothiophene derivatives and thus appears to be a useful tool for the synthesis of extended sulfur-containing heteroacenes. The incorporation of sulfur is unambiguously preprogrammed via the positions of fluorines in the precursors, allowing the selective synthesis of extended thienoacenes with up to 96% yield.
CRIS-Team Scopus Importer:2021-11-26